A Selective "Turn‐On" Fluorescent Probe for Recognition of Mercury(II) Ions in Aqueous Solution Based on a Desulfurization Reaction. Issue 7 (5th June 2013) - Yan, Yuanyuan; Zhang, Yanhua; Xu, Hui
<x xml:space="preserve">Abstract</x> Turn me on: A new "turn‐on" 1, 8‐naphthalimide‐type chemosensor 1 has been prepared and exhibited high selectivity and sensitivity towards Hg2+ ions over other heavy‐ and transition‐metal ions in aqueous solution, accompanied by the transformation of a weakly fluorescent thiourea moiety (colorless) to a highly fluorescent urea one (green) with an increase in fluorescence intensity.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>